Unintended Effects of the Bologna Reforms - Reichert, Sybille (International Higher Education, 2009)
The Bologna reform process has resulted in some unintended effects. At the system level, the four effects are: creating a dense network as an osmosis; stimulated reforms as a catalyst; shifting to vocational orientation; and structuring mass vs. elite degrees. At the institutional level, strengthening the central leadership, crosscutting the vertical boundaries among continental European universities, strengthening stakeholder influence.